(3GdHMQ GdcHjQ aj HMK GdJaSjQs - (3CMeO Hf eMeO Hf efUhQ , GHf GdoenfpqjQ GdpqSncrfnOQj,J (B683 (3g` s
(3ChdgG (B:s
(3jHJOF HJaSjQ bhdg JYGdi (B: (3Jdc GdQSd aVdfG HYVge Ydi HYV (B" (3ef ShQI GdHbQI s
(3BNQgG (B:s
(3jfJgi HBNQ ShQI (B" (3Bd YeQGf (B" s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B220 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B161s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B166 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B21 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3JaSjQ (B60) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs